Research hotspots and new trends in the impact of resistance training on aging, bibliometric and visual analysis based on CiteSpace and VOSviewer - Mi, Junmin; Zhang, Litao; Sun, Wei; Wang, Zhen; Yang, Pengbo; Zhang, Jiachen; Zhang, Yani (Frontiers in Public Health, 2023)
Purpose Resistance training (RT) can intervene in aging, which can effectively improve trainees’ life. However, unhealthy living habits such as irregular life, obesity and hyperlipidemia, and chronic diseases lead to a significant decline in the energy level of the population, seriously affecting the health of the population. Our research identifies the research hotspots of RT to intervene in aging from the perspective of bibliometrics, predicts research frontiers and development trends, and provides more perspectives for research on aging populations. Methods In this study, we used CiteSpace and VOSviewer visualization software to draw the scientific knowledge map of countries/regions, institutions, authors, co-occurrence keywords, and co-cited references of published articles, and explore the Web of Science core collection database all about the RT intervention aging research status, hotspots, frontiers, and development trends of articles on aging. Results Among the 760 articles that meet the inclusion criteria, the number of articles published and the frequency of citations have increased steadily in the past 5 years. Judging from the countries/regions, institutions, scholars, and journals that published articles, the ones with the largest numbers are the USA, Univ Estadual Londrina, Cyrino ES, and Exp Gerontol. The ones with the highest influence are England, Univ Arkansas Med Sci, Frontera WR, and Biochem Biophys Rep Co. The top five co-occurrence keywords of include exercise, strength, resistance training, skeletal muscle, and muscle strength. The research frontier is physical function. Conclusion In the field of RT intervention aging research, relevant scholars deserve further in-depth research and exploration. The United States, Brazil, Canada, and other economically developed countries/regions, institutions, and authors have greater influence and productivity. These quantitative research results can provide references for relevant scholars’ follow-up research and government departments to formulate and modify health policies or measures.